Glial receptor PLXNB2 regulates schizophrenia-related stress perception via the amygdala - Xuan, Fang-Ling; Yan, Ling; Li, Yanli; Fan, Fengmei; Deng, Hu; Gou, Mengzhuang; Chithanathan, Keerthana; Heinla, Indrek; Yuan, Liang; Seppa, Kadri; Zharkovsky, Alexander; Kalda, Anti; et al. (Frontiers in Immunology, 2022)
Stress is a trigger for the development of psychiatric disorders. However, how stress trait differs in schizophrenia patients is still unclear. Stress also induces and exacerbates immune activation in psychiatric disorders. Plexins (Plxn) and its ligands semaphorins (Sema) are important cellular receptors with plural functions in both the brain and the immune system. Recently, the role of Plxn/Sema in regulation of neuroinflammation was also noticed. Here, when investigating immune mechanisms underlying stress susceptibility in schizophrenia, we discovered the role of Plxnb2 in stress response. Patients of first-episode schizophrenia (FES) with high stress (FES-hs, n=51) and low stress (FES-ls, n=50) perception and healthy controls (HCs) (n=49) were first recruited for neuroimaging and blood bulk RNA sequencing (RNA-seq). A mouse model of chronic unpredictable stress (CUS) and intra-amygdaloid functional blocking of Plxnb2 were further explored to depict target gene functions. Compared to HCs, FES-hs patients had bigger caudate and thalamus (FDR=0.02&0.001, respectively) whereas FES-ls patients had smaller amygdala (FDR=0.002). Blood RNA-seq showed differentially expressed PLXNB2 and its ligands among patient groups and HCs (FDR<0.05 0.01). Amygdaloid size and PLXNB2 level were both negatively correlated with stress perception (p<0.01&0.05, respectively), which fully mediated the amygdaloid positive association with PLXNB2 expression (β=0.9318, 95% CI: 0.058 1.886) in FES-hs patients. In mice, Plxnb2 was enriched in astrocytes and microglia and CUS reduced its expression in astrocytes (p<0.05). Inhibition of amygdaloid Plxnb2 by its functional blocking monoclonal antibody (mAb)-102 induced mice anxiety (p<0.05), amygdaloid enlargement (p<0.05), and microglial ramification (p<0.001) compared to saline. These data suggest that PLXNB2 regulates amygdala-dependent stress responses.